III-harmonic Curves in SL2ℝ˜\widetilde {{\rm{S}}{{\rm{L}}_2}\mathbb{R}} Space - Senoussi Bendehiba (Annals of the West University of Timisoara: Mathematics and Computer Science)
Some work has been done in the study of non-geodesic III-harmonic curves in some model spaces. In this paper, we study III-harmonic curves in SL2ℝ˜\widetilde {{\rm{S}}{{\rm{L}}_2}\mathbb{R}} space. We give necessary and su cient conditions for helices to be III-harmonic. Also, we characterize III-harmonic curves in terms of their curvature and torsion.